A narrative review exploring advances in interval training for endurance athletes - Mølmen, K. S.; Rønnestad, B. R. (Applied Physiology, Nutrition, and Metabolism, 2024)
Interval training is considered an essential training component in endurance athletes. Recently, there has been a focus on optimization of interval training characteristics to sustain a high fraction of maximal oxygen consumption (=90% VO2max) to improve physiological adaptations and performance. Herein, we present a synopsis of the latest research exploring both acute and chronic studies in endurance athletes. Further, a decision flowchart was created for athletes and coaches to select the most appropriate interval training regime for specific individualized goals.